Effects of age and sex on field-based measures of muscle strength and power of the upper and lower body in adolescents. Issue 9 (3rd May 2021) - Hackett, Daniel A.; He, Wu; Orr, Rhonda; Sanders, Ross
ABSTRACT: Field-based tests including the medicine ball chest throw (MBCT) and vertical jump are used to assess muscle performance. To date no study has compared performances of these field-based tests in adolescents across a range of ages. The aim of this study was to examine the effects of age and sex on MBCT and countermovement jump (CMJ) performance in adolescents.This cross-sectional study involved 2192 adolescents (1477 males and 715 females) aged between 12 and 17 years. Trials of the MBCT and CMJ were performed with CMJ peak power estimated. Males had significantly greater MBCT distance, CMJ height and CMJ peak power at each consecutive age group separated by 1 year (p < 0.001). Females generally showed significantly greater performances across a larger age range of at least 2 years for MBCT (p ≤ 0.004) and CMJ peak power (p ≤ 0.018). Males had greater performances than females for MBCT distance, CMJ height, and CMJ peak power from 13 years and above (p < 0.001). Sex differences widened with increasing age for all tests from 5-8% at 12 years progressing to 24–29% at 16–17 years. This study shows the effects of age and sex is similar for both the MBCT and CMJ tests in adolescents.